Child Abuse: A Review Article: Pelecehan terhadap anak: Sebuah Artikel Ulasan - Essa, Hajer S. (Universitas Muhammadiyah Sidoarjo, 2024)
In numerous clinical settings, therapists frequently encounter child maltreatment, including physical, sexual, and emotional abuse, as well as other forms, which are associated with a markedly increased risk for both concurrent and subsequent psychopathology. Assessing children who have experienced abuse typically takes longer than evaluating youngsters who have not. Young children—who experience the highest rates of maltreatment—present especially difficult tests because of their acute reliance on their caregiving environments. Highlights: Child maltreatment increases risk of psychopathology. Assessment takes longer for abused children. Young children are especially vulnerable due to caregiver dependence. Keywords: Child Abuse, Review.